2020
DOI: 10.1002/lno.11608
|View full text |Cite
|
Sign up to set email alerts
|

Highly enriched N‐containing organic molecules of Synechococcus lysates and their rapid transformation by heterotrophic bacteria

Abstract: Phytoplankton are major contributors of labile dissolved organic matter to marine euphotic zone ecosystems. Viral-mediated phytoplankton lysis releases a considerable amount of bioavailable cellular contents and facilitates localized heterotrophic bacterial growth. The rapid turnover times of this labile organic matter renders it difficult to trace their transformation within natural environments. In the present study, we used a model phototroph-heterotroph coculture system to investigate the organic molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 70 publications
5
34
0
Order By: Relevance
“…Virus-lysed DOM are regarded as labile for prokaryotic utilization ( Middelboe and Jørgensen, 2006 ) and can be quickly utilized by other heterotrophic prokaryotes ( Zheng et al, 2020 ). Here, we estimated the abundance – using the estimated volume of infected cells – and the contribution of lysed DOM to the DOM pool in Lake Biwa.…”
Section: Discussionmentioning
confidence: 99%
“…Virus-lysed DOM are regarded as labile for prokaryotic utilization ( Middelboe and Jørgensen, 2006 ) and can be quickly utilized by other heterotrophic prokaryotes ( Zheng et al, 2020 ). Here, we estimated the abundance – using the estimated volume of infected cells – and the contribution of lysed DOM to the DOM pool in Lake Biwa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on blooms has primarily focused on the microbial community, potential functions, and some chemical signals [7], while only a few studies have been conducted on the composition of DOM, whereas phytoplankton are a major dissolved organic nitrogen (DON) source [32,33]. Cultivated marine Synechococcus is reported to contribute a variety of nitrogen-rich compounds to DOM, including amino acids, oligopeptides as well as nucleosides, and indoles [34,35]. Geider et al [36] found cyanobacteria and diatoms contain 30-60% proteins by dry weight, which are the largest compounds; however, dinoflagellates released more nitrogen-containing substances, while diatoms also released a considerable amount of carbohydrates such as polysaccharides.…”
Section: Characterization Of In Situ Dom By Untargeted Analysismentioning
confidence: 99%
“…Some viruses infecting phytoplankton have strategies to cope with nutrient limitation within their host, for example, by minimizing interference with N‐fixation (Kuznecova et al 2020) or manipulation of host metabolism to boost N or P uptake (Monier et al 2012, 2017). These strategies can result in a reduced carbon:nutrient content of infected versus healthy host tissue (Ankrah et al 2014), stimulating viral reproduction, but also enriching the quality of the cell material released in the water after cell lysis (Ankrah et al 2014, Zheng et al 2020). Pathogens may indirectly alter plant chemistry by inducing plants to reallocate nutrients as a defense mechanism.…”
Section: Other Factors Masking Stoichiometrically Driven Trendsmentioning
confidence: 99%